Assessing the Likelihood of Gene Flow From Sugarcane (Saccharum Hybrids) to Wild Relatives in South Africa - Snyman, Sandy J.; Komape, Dennis M.; Khanyi, Hlobisile; van den Berg, Johnnie; Cilliers, Dirk; Lloyd Evans, Dyfed; Barnard, Sandra; Siebert, Stefan J. (Frontiers in Bioengineering and Biotechnology, 2018)
Pre-commercialization studies on environmental biosafety of genetically modified (GM) crops are necessary to evaluate the potential for sexual hybridization with related plant species that occur in the release area. The aim of the study was a preliminary assessment of factors that may contribute to gene flow from sugarcane (Saccharum hybrids) to indigenous relatives in the sugarcane production regions of Mpumalanga and KwaZulu-Natal provinces, South Africa. In the first instance, an assessment of Saccharum wild relatives was conducted based on existing phylogenies and literature surveys. The prevalence, spatial overlap, proximity, distribution potential and flowering times of wild relatives in sugarcane production regions based on the above, and on herbaria records and field surveys were conducted for Imperata, Sorghum, Cleistachne and Miscanthidium species. Eleven species were selected for spatial analyses based on their presence within the sugarcane cultivation region: four species in the Saccharinae and seven in the Sorghinae. Secondly, fragments of the nuclear internal transcribed spacer (ITS) regions of the 5.8s ribosomal gene and two chloroplast genes, ribulose-bisphosphate carboxylase (rbcL) and maturase K (matK) were sequenced or assembled from short read data to confirm relatedness between Saccharum hybrids and its wild relatives. Phylogenetic analyses of the ITS cassette showed that the closest wild relative species to commercial sugarcane were Miscanthidium capense, M. junceum and Narenga porphyrocoma. Sorghum was found to be more distantly related to Saccharum than previously described. Based on the phylogeny described in our study, the only species to highlight in terms of evolutionary divergence times from Saccharum are those within the genus Miscanthidium, most especially M. capense and M. junceum which are only 3 million years divergent from Saccharum. Field assessment of pollen viability of 13 commercial sugarcane cultivars using two stains, iodine potassium iodide and triphenyl tetrazolium chloride, showed decreasing pollen viability (from 85 - 0%) from the north to the south eastern regions of the study area. Future work will include other aspects influencing gene flow such as cytological compatibility and introgression between sugarcane and Miscanthidium species.